Report on Responsible Research and Innovation (RRI) Workshop - Hadley Kershaw, Eleanor; Hartley, Sarah; Pearce, Warren (University of Nottingham, 2015)
The potential for an ongoing interdisciplinary conversation about RRI at the University of Nottingham (UoN) was identified during a research project conducted in summer 2014 to investigate how RRI is being interpreted within UoN (Pearce et al., 2014). On 8th January 2015, following a public lecture by Professor Richard Owen, University of Exeter, on ‘Responsible Research and Innovation: From nice words to meaningful action’, 18 participants from 11 schools and departments across UoN gathered to address the following workshop aims: 1. Establish an RRI network across UoN; 2. Share understandings of RRI from different perspectives and disciplines; 3. Explore what the RRI agenda means, how we might want to respond and what support might be needed.